Enhancing Grammar Proficiency Through PjBL: A Study on Student-Generated Questions for Tense Mastery and Communication Skills - Almas Rifqi Darmawan; Melia Dwi Renovriska (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2025)
Project-Based Learning is an approach to enhance students’ skill in certain aspects such as critical thinking, problem solving, and foster practical skills needed in the approach. This research aims to describe how student-generated grammar questions as a PjBL can be used systematically in the classroom. This research used a qualitative method employing observation and documentation as approaching tools. The study examined five groups, with Group 1 standing out as the most confident—all members delivered presentations successfully and answered grammar questions on tenses, subject-verb agreement, and conjunctions. In contrast, Groups 2–5 showed lower confidence, particularly in reading questions, though Group 4 had one fluent speaker. Question types varied: Group 2 tackled tenses and subject-verb agreement, Group 3 faced fill-in-the-blank and noun-related questions, and Groups 4–5 dealt with tenses, fill-in-the-blank, and noun/adjective questions. Notably, tenses were a recurring theme across all groups, underscoring their importance in the assessment. This method not only strengthens their understanding of linguistic structures but also directly enhances their writing skills, as they learn to apply these rules contextually and transforms grammar learning into an interactive, empowering process that cultivates both accuracy and expressive ability.